The Impact of Realia Media on Elementary School Students' Learning Achievement: An Experimental Study on Science Subjects - Yaam, Yulianti Martina; Fitriani, Anis Alfian; Saputro, Isnaini Eddy (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aimed to assess the impact of realia media on the scientific learning achievement of fourth-grade pupils. This study employed a pre-experimental design utilizing a quantitative research methodology. This research was carried out at Elementary School Inpres 18 in Sorong Regency, using a sample of 30 children. This study utilized observation sheets for teachers and students, along with multiple-choice exam items. The data analysis employed the SPSS 25 software. The findings indicated that the mean score for teacher and student evaluations was 100%, meeting excellent standards. The investigation of student learning completeness yielded an average pretest score of 4.46 and a posttest score of 6.96. The N-Gain test yielded an average pretest score of 0.45, indicating it falls within the moderate range with a reasonably effective level of efficacy. Consequently, it is determined that realia media positively influences student learning achievement in science topics, rendering them more engaging and effective, thereby enhancing student performance as evidenced by the N-Gain test results.